2015
DOI: 10.1044/2015_jslhr-l-14-0341
|View full text |Cite
|
Sign up to set email alerts
|

Formulaic Language in Parkinson's Disease and Alzheimer's Disease: Complementary Effects of Subcortical and Cortical Dysfunction

Abstract: Purpose: The production of formulaic expressions (conversational speech formulas, pause fillers, idioms, and other fixed expressions) is excessive in the left hemisphere and deficient in the right hemisphere and in subcortical stroke. Speakers with Alzheimer's disease (AD), having functional basal ganglia, reveal abnormally high proportions of formulaic language. Persons with Parkinson's disease (PD), having dysfunctional basal ganglia, were predicted to show impoverished formulaic expressions in contrast to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 104 publications
1
24
0
Order By: Relevance
“…Formulas can therefore be seen as enabling communication, however they also limit the scope of communication and are less suited for novel situations or expressing new ideas (Wray, 2011). While an increase in formulaic language has been observed in aphasia and dementia, there are reports of decreased use of formulas in speakers with right hemisphere damage (Van Lancker Sidtis & Postman, 2006) and also in Parkinson's disease (Van Lancker Sidtis, Choi, Alken, & Sidtis, 2015). Van Lancker and collaborators interpret these data as support for a dual-process model, in which novel/analytic language is largely dependent upon left hemisphere computational mechanisms, while formulas are represented in the right hemisphere and subcortical structures (see also Van Lancker Sidtis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Formulas can therefore be seen as enabling communication, however they also limit the scope of communication and are less suited for novel situations or expressing new ideas (Wray, 2011). While an increase in formulaic language has been observed in aphasia and dementia, there are reports of decreased use of formulas in speakers with right hemisphere damage (Van Lancker Sidtis & Postman, 2006) and also in Parkinson's disease (Van Lancker Sidtis, Choi, Alken, & Sidtis, 2015). Van Lancker and collaborators interpret these data as support for a dual-process model, in which novel/analytic language is largely dependent upon left hemisphere computational mechanisms, while formulas are represented in the right hemisphere and subcortical structures (see also Van Lancker Sidtis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Production competence arises from the basal ganglia, a collection of subcortical nuclei, where motor gestures are facilitated, utilizing procedural memory (Ullman, 2004;Graybiel, 2005Graybiel, , 2008Mishkin, Malamut, & Bachevalier, 1984). Persons with Parkinson's disease, who suffer from dysfunction of the basal ganglia, produce significantly fewer familiar phrases than matched healthy speakers (Illes, 1989; Van Lancker Sidtis, Choi, Alken, & Sidtis, 2016;Bridges, Van Lancker Sidtis, & Sidtis, 2013).…”
Section: Neurolinguistic Evidencementioning
confidence: 97%
“…Given that performance varied with speech modes, as has been reported (1219), structured sets, representing selected differing modes were created and offered during therapy. Previous studies have revealed that motor speech efficacy differs for conversation and repetition (1218).…”
Section: Participant Descriptionmentioning
confidence: 99%
“…Previous studies have revealed that motor speech efficacy differs for conversation and repetition (1218). Other studies suggested that formulaic and novel expressions are differently processed in the brain (19). Current work with the participant indicated more successful production on continuously voiced material.…”
Section: Participant Descriptionmentioning
confidence: 99%